Comparative Outcomes of Septoplasty with and without Intranasal Splintage - Abdul Manan Khan, Aria Masoom (Pakistan Journal of Medical & Health Sciences, 2023)
Background: For septal deviations, septoplasty is a frequently utilized procedure in outpatient clinics. A common technique for symptomatic nasal septal deviation is septoplasty. After surgery, it facilitates nasal airflow. Objective: To assess the comparative outcomes of Septoplasty with and without Intranasal Splintage Methodology: The current randomized controlled trial was conducted at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from March 2023 to August 2023 after taking approval from the research committee of the institute. Totally 100 patients were included in our study based on WHO formula for calculation of sample size. Using the lottery approach, the patients were categorized into two groups. Intranasal splintage packing was applied to patients in group A, however intranasal splintage was not applied to patients in group B. SPSS 24 Version was used to enter and analyze all of the research data. Results: In group A, the mean (SD) age was 22.6 ( ±3.51) years whereas in group B, it was 23.4 ( ±4.11). (p=0.21) The male patients in group A were 31 (62%) and female were 19 (38%) whereas in group B, male patients were 32 (64%) and female were 18 (36%). (Figure 1) In group A, mild, moderate and severe post-operative pain was observed in 16 (32%), 26 (52%) and 8 (16%) respectively while in group B, the mild, moderate and severe post-operative pain was observed in 19 (38%), 20 (40%) and 11 (22%) respectively. (P=0.091) A significant difference was observed in case of postoperative bleeding. In group A, crusting was observed in 16 (32%) patients and no crusting was observed in 34 (68%) patients whereas in group B, crusting was observed in 11 (22%) patients and no crusting was observed in 39 (78%) patients (p=0.091). Conclusion: With the exception of postoperative bleeding, our research finds that the results of septoplasty with splints are not substantially different from those without splints. Keywords: Septoplasty; Intranasal; Splintage